Phytochemical analysis of Momordica balsamina L. fruits (IASH Indian Journal of Arid Horticulture, 2024)
Momordica balsamina L., commonly known as balsam apple or African pumpkin, is a vegetable with high nutritional value. It contains bioactive compounds with medicinal properties and has been extensively used in traditional medicine to treat a range of ailments, including malaria, fevers, and diabetes. This study focused on analyzing the bioactive compounds in Momordica balsamina fruits using GC-MS/MS. A total of 100 bioactive compounds were detected in the green fruits, while 109 were identified in the ripe fruits. These compounds exhibit significant pharmacological properties and have the potential to be used in the treatment of various human diseases.